2020
DOI: 10.9734/jpri/2020/v32i1930711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Releasing Oral Gel Compared to Chlorhexidine Gel in the Treatment of Periodontitis

Abstract: The aim of the current study is to compare the effect of oxygen releasing oral gel and chlorhexidine gel in the treatment of periodontitis and the objective was to assess and compare the changes in clinical parameters such as Probing pocket depth, Bleeding on probing, Clinical attachment levels between oxygen releasing oral gel and chlorhexidine gel. The current pilot study which compares oxygen releasing gel with chlorhexidine gel is a randomised split mouth clinical trial .All the patients included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Studies have demonstrated a significant shift in microbial composition toward a homeostasis state of biofilm after applying oxygen therapy ( Fernandez, 2014 , Filoche et al, 2010 , Fernandez y Mostajo, M., Exterkate, R.A., Buijs, M.J., Crielaard, W., Zaura, E., , 2017 ). Niveda and Kaarthikeyan reported a significant reduction in probing pocket depth in patients with chronic periodontitis treated with blue®m oxygen therapy, confirming its clinical advantage on periodontitis ( Niveda, and Kaarthikeyan, 2020 ). Toothpastes containing active oxygen and lactoferrin have been proven to have comparable antiplaque and antigingivitis efficacies compared to triclosan-containing toothpastes ( Cunha et al, 2019 ).…”
Section: Clinical Applications Of Topical Oxygen Therapymentioning
confidence: 84%
“…Studies have demonstrated a significant shift in microbial composition toward a homeostasis state of biofilm after applying oxygen therapy ( Fernandez, 2014 , Filoche et al, 2010 , Fernandez y Mostajo, M., Exterkate, R.A., Buijs, M.J., Crielaard, W., Zaura, E., , 2017 ). Niveda and Kaarthikeyan reported a significant reduction in probing pocket depth in patients with chronic periodontitis treated with blue®m oxygen therapy, confirming its clinical advantage on periodontitis ( Niveda, and Kaarthikeyan, 2020 ). Toothpastes containing active oxygen and lactoferrin have been proven to have comparable antiplaque and antigingivitis efficacies compared to triclosan-containing toothpastes ( Cunha et al, 2019 ).…”
Section: Clinical Applications Of Topical Oxygen Therapymentioning
confidence: 84%
“…The group treated with oxygen-releasing gel showed better potential for reducing the probing depth. 9 When used to treat periodontitis, active oxygen in gel form selectively eradicates the anaerobic bacteria associated with the condition, promoting the recovery of healthy oral flora. 10 This clinical result corroborates the findings of the in vitro study, which showed that blue ® m oral gel reduced a smaller number of bacterial species when compared to chlorhexidine during subgingival biofilm formation, but it was better than chlorhexidine in reducing red-complex bacterial proportions.…”
Section: Discussionmentioning
confidence: 99%
“…The group that was treated with the oxygen-releasing oral gel showed better potential in probing depth reduction. The authors emphasized that thorough sub-gingival scaling and root planning, along with adjuvant tOT, aid in reducing periodontal pockets [ 80 ]. Active oxygen in a gel form used for the treatment of periodontitis selectively eradicates the anaerobic bacteria associated with periodontitis to promote the recovery of a health-compatible oral flora [ 81 ].…”
Section: Oxygen Therapymentioning
confidence: 99%